BOARDING SCHOOL MANAGEMENT IN DEVELOPING CHILD-FRIENDLY EDUCATION - ASR Maulana Al Azizi; Muhammad In’am Esha; Nurul Yaqien (Jurnal Manajemen Pendidikan, 2026)
Child-friendly education is a crucial issue in the management of Islamic educational institutions, including Islamic boarding schools (pesantren), given the complexity of the relationships between care, learning, and the lives of students in a boarding system. This study aims to describe the management of Islamic boarding schools in developing child-friendly education at the Alhayatul Islamiyah Kedungkandang Islamic Boarding School in Malang City. The study employed a qualitative approach with a case study design. The subjects included the boarding school's caretakers, administrators, ustadz/ustadzah (Islamic teachers), and students who were selected purposively. Data collection techniques were conducted through observation, in-depth interviews, and documentation studies. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing, with data validity maintained through triangulation of sources and techniques. The results indicate that Islamic boarding school management in developing child-friendly education is carried out through planning child-protection-oriented care programs, implementing humanistic parenting patterns, strengthening educator professionalism, and continuous monitoring and evaluation. This study concludes that the success of child-friendly education in Islamic boarding schools is largely determined by managerial commitment, the exemplary behavior of caregivers, and an institutional culture that upholds Islamic and humanitarian values.